Study of housing conditions among people of a rural community in Morang, Eastern Nepal - Acharya, Alok; Pokhrel, Ava; Yadav, Amar Kumar; Mishra, Rimu (Journal of Nobel Medical College, 2018)
Background : Poor Housing condition, sanitation and hygiene is associated with adverse health conditions. This study is done to assess the housing conditions, sanitation coverage and hygiene practices among rural community in Bhaudaha VDC, eastern Nepal. Material &Methods: A cross sectional study was conducted from 22nd May 2016 to 22nd November 2016 in Bhaudaha VDC of eastern Nepal with appropriated sample size of 525 participants. A direct interview was taken with structured questionnaire. Chi square test was used to find out association of the variables. Results: Out of 525 respondents, adequate ventilation was present among 54.9% literates followed by 44.2% illiterates (p=0.01) and separate kitchen was also found among 77.2% of literates and 64.6% of illiterates (p=0.002). Among Dalit castes 74.4% had separate kitchen in their house followed by 50.7% janajatis (p<0.001). Covering of stored water was found in 75.8% Dalit and 61.2% Janajati (P=0.003). Improved sanitation was highest among other terai casts (78.1%) followed by Dalits (59.9%) and 58.2% Janajati (p=0.132). Conclusion: There is need of appropriate methods of health education to be focused on all the groups in the community for improvement in sanitation and healthy housing conditions and targeted more towards Janajati and illiterate group and further studies need to be done in different region of Nepal to understand the cause of disparities in housing and sanitation conditions among different groups. Journal of Nobel Medical College Volume 6, Number 2, Issue 11 (July-December, 2017) Page: 1-8